(3MGTjI Ydi TQM GdCQOHjdj ddCfehPL aj GdfMh ddReNTQjs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj UQa Edi fMh , fMh aUd GdYHGO ef cd HGHs
(3BNQgG (B:s
(3hgh GdGHJOGA edMb HGdaGYd NHQ ddeHJOC, GdeHJOC hGdNHQ LedI GSejI JQcjH ESfGOj GHJOGFj dG eMd dg ef GdEYQGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 61s
(3eYLe GdeDdajf(B: 3 / 176s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs